(Benzofuran-2-yl)(3-methyl-3-phenylcyclobutyl)methanone - Yüksektepe, Ç; Saraçoglu, H; Koca, M; Çukurovali, A; Çaliskan, N (Int Union Crystallography, 2004)
The structure of the title compound, C20H18O2, consists of a dimeric arrangement of benzofuran molecules around an inversion centre, linked via C - H...O hydrogen bonds. There are also C - H...pi ring interactions. All these interactions result in the formation of infinite chains parallel to the [ 100] axis. The cyclobutane ring is puckered, with a dihedral angle of 29.03 (13)degrees between the two three-atom planes.